Prevalence and predictors of undernutrition among under -5 children in slum of Gwalior city - Gupta, Rajesh; Shukla, Durgesh; Mishra, Ashok; Bansal , Manoj; Mungi, Sasmita (Indian Journal of Community Health, 2020)
Background: Under-nutrition in young children has long-term negative effects on physical and cognitive development. Under nutrition problems are affecting overall development of the country. Aim and Objectives: This study was undertaken to assess the prevalence and to examine predictors of undernutrition among children of less than 5 years of age in urban slum of Gwalior district. Materials and Methods: A community based cross sectional study was conducted on 550 children with age group 6 months to 5 years residing in urban slum. Chi square test and logistic regression were performed to see association and to predict risk factors. Results: Undernutrition was prevalent among 68% children. Unreserved category(UR) was found to be at lesser risk as compared to SC/ST (OR: 0.238 ;CI : 0.133-0.423).Nuclear families had more risk for undernutrition as compared to Joint families (OR:1.947;CI: 1.352-2.803),Illiterate mothers showed more risk (OR:5.696 ,CI:2.791-11.625) ,Similar results were obtained for illiterate fathers (OR: 3.950; CI:1.868-8.353) as compared to fathers having qualification of at least graduation. Females with one parity were protective for undernutrition (OR: 0.411; CI: 0.182-0.928).Low birth weight (OR: 1.996; CI: 1.332-2.991) and total member in family also played a significant role. Conclusion: Poverty and education predispose undernutrition in slum children. There is a need to undertake intervention through community education regarding breastfeeding, ANC, birth spacing and to adopt practices that favour good nutrition of child.